"Prison didn't change me, I have changed": Narratives of change, self, and prison time. (November 2022) - Maier, Katharina; Ricciardelli, Rosemary
Drawing on interview data with over 50 male former prisoners in Ontario, Canada, we examine male ex-prisoners' narratives of change within prison settings. Specifically, we focus on how ex-prisoners talk about change to self and their persona, as they reflect back on both their pre-prison selves and the ways they believe prison changed them. We find that these ex-prisoners described prison as a time where they developed a more general sense of positive change. Ex-prisoners described how prison living made them "calmer, " "stronger, " and more "patient" overall. These descriptions stand in tension with the overall hostility of prison environments where prisoners are forced to focus on survival and basic well-being as they navigate the risks and threats of prison living. Overall, in this article, we seek to contribute to emerging discussions on positivity within prison settings, acknowledging that studying the more positive impacts of prison is a delicate yet important endeavor necessary to help better understand the experiential complexities of punishment.